Pengetahuan tentang Anemia dengan Kadar Hemoglobin Remaja Putri - Arifarahmi Arifarahmi (Universitas Baiturrahim, 2021)
WHO mentions that anemia is the 10 biggest health problems at this time. One of the groups at high risk of suffering from anemia are school-age children and adolescents. Lack of one nutrient can cause a disease in the form of a deficiency disease. In adolescents, iron deficiency can reduce work performance and learning achievement in addition to decreased body resistance to infectious diseases.Knowledge about anemia is important in preventing adolescent girls from having normal hemoglobin levels. If the knowledge of adolescent girls about anemia is good, it is hoped that will not experience anemia. The purpose of this study was to determine the relationship between knowledge about anemia and hemoglobin levels in adolescent girls. The study was carried out at SMPN 14 Jambi City, and used an analytical research design. The research population was adolescent girls, with 30 respondents. The research instrument used a questionnaire and a hemoglobin measurement tool, as well as an informed consent sheet and a permit signed by the parents. The data collected were analyzed by univariate and bivariate.The results of this study showed that 30 respondents, most of the adolescent girls have good knowledge, namely 26 people (86.7%), and 29 people who do not have anemia (96.7%). The results of the bivariate test showed that there was no relationship between knowledge about anemia and hemoglobin levels p-value = 0.867. Furthermore, it is necessary for adolescent girls to check their hemoglobin levels regularly as an effort to determine their health status